Role of microbiological culture and polymerase chain reaction (PCR) of actinomyces in medication-related osteonecrosis of the jaw (MRONJ). Issue 3 (March 2017) - Panya, Sappasith; Fliefel, Riham; Probst, Florian; Tröltzsch, Matthias; Ehrenfeld, Michael; Schubert, Sören; Otto, Sven
Abstract: We hypothesized that local infection plays a critical role in the pathogenesis of medication-related osteonecrosis of the jaw (MRONJ). Recent developments in molecular methods have revolutionized new approaches for the rapid detection of microorganisms including those difficult to culture. The aim of our study is to identify the bacterial profiles in MRONJ by microbiological culture and polymerase chain reactions (PCR). A retrospective analysis was performed on MRONJ patients from 2008 to 2014. The bacterial profile from MRONJ bone samples was determined using microbiological culture and PCR. Ninety five patients fulfilled the inclusion criteria with mean age of 69.85 ± 8.71 years. A female predilection was detected. The mandible was more commonly affected than maxilla. Tooth extraction was the frequent triggering factor. Breast cancer was the primary cause for administration and intravenous bisphosphonates were the most commonly administrated antiresorptive drugs. The majority of patients were classified as stage 2. Posterior teeth were most commonly affected. Based on bone culture results, the most common microorganism were both actinomyces and mixed flora. PCR confirmed the presence of actinomyces in 55 patients. Our data suggest that PCR might be an innovative method for detection of microorganisms difficult to culture using traditional microbiological techniques. Highlights: We hypothesized that local bacterial infections plays a critical role in the pathogenesis of medication-related osteonecrosis of the jaw (MRONJ) Bacterial profile of MRONJ bone samples was determined using microbiological culture and PCR. Actinomyces were the most frequent microorganisms in the disease. However, this does not necessarily lead to the pathogenic role. PCR was found to be the most reliable method for the detection of these microorganisms.